Synthesis of polyoxazolidines and their application in moisture-curable polyurethane. Issue 12 (17th June 2016) - Ming, Shi; Hong, Chen; Jun, Gao; Jingxin, Lei
Abstract: A series of polyoxazolidines based on monofunctional oxazolidine were designed and successfully synthesized by transesterification reaction. Their structures were characterized by 1 H NMR, 13 C NMR, FI-IR, ESI-MS, and elemental analysis. FI-IR spectroscopy was used to study the kinetics of oxazolidines hydrolysis reactions. Furthermore, the applications of resulting oxazolidines as latent curing agents in single-component polyurethane (SPU) systems were investigated. The experimental results showed that the pure SPU specimen cured under atmospheric moisture formed lots of foaming and presented serious swelling. In contrast, the SPU specimens including oxazolidines and latent curing agents displayed considerable enhancement in the mechanical properties, apparent performance, and curing rate. Compared with SPU–OXi curing samples, the tensile strength of the SPU-OX2 reached up to 1.78Mpa, and the elongation at break increased to 533.0%, resulting from the dual effects of the high cross-linking density and the urethane group in OX2 .